Tongue microbiota and pathological processes: a pilot autopsy study - Aparecida de Lima Pereira, Sanivia (2017)
Context: Human general health may be mirrored in oral changes, and oral lesions can hallmark systemic diseases.Diverse pathological processes and numerous infectious agents have been described in the human oral cavity.Autopsy reports of the association among oral pathogens, tongue pathological changes, and systemic diseases are still lacking.Aim: To describe pathological processes and infectious agents found in the tongues of necropsied patients, and comment the data from coexistent systemic disease.Design: Cross sectional study.Setting and Participants: Twenty-four complete autopsies of adults were randomly selected in a Brazilian University Hospital.Main Outcomes Measures: After macroscopic evaluation, the tongues were longitudinally sectioned and the tissue samples were submitted to the histological routine.Results: The histopathology changes were: hydropic degeneration (83.3%), atrophy (75%), inflammation (70.8%), necrosis with ulceration (70.8%), hypertrophy (58.3%), necrosis without ulceration (16.6%) and arteriolar hyalinosis (4.2%). The microbiota consisted of: bacteria (54.2%), Candida sp (25%), Cryptococcus sp (4.2%) and Malassezia furfur (4.2%). Bacteria were found on the tongues from all the patients with rheumatic cardiopathy or pyelonephritis, in 44.4% of the patients with bronchopneumonia and in 40% of the patients with esophagitis. Half of AIDS patients presented Candida sp hyphae associated with tongue inflammation, necrosis and ulceration.Conclusions: Although not always associated to gross lesions, the tongue microbiota can cause pathological processes. As oral pathology has been associated with systemic diseases, workers in health care should develop a higher awareness about the role of tongue changes in the general health.